Education and the labour market in Latin America : why measurement is important and what it tells us about policies, reforms and performance - Carlson, Beverley A. (ECLAC SantiagoCL, 2001)
Examines two pivotal education and labour market policy and performance questions viz. the degree to which countries in the Latin American region are catching up or falling behind their competitors in the area of human capital formation with particular reference to upper secondary and technical education; the degree to which higher educational attainment in Latin America countries results in positive labour market outcomes including labour force participation, employment and unemployment, and earnings.